Идентификация и моделирование теплофизических процессов в строительных конструкциях при экстремальных тепловых воздействиях - Мацевитый, Ю.М.; Слесаренко, А.П.; Сафонов, Н.А. ("Доповіді НАН України", 2007)
An inverse heat conduction problem on determining the influence of the flame temperature on building constructions during a conflagration has been solved by the thermophysical experiment data on the base of the combined use of the straight lines method, method of iterations, and structural and variational methods. Variations of the time-dependent flame temperature and the temperature fields of building columns of rectangular cross-sections have been determined.